Driftless Dark Skies Initiative: Training Astronomy Educators - Kiesau, Jonel; Heasley, John (Proceedings of the Wisconsin Space Conference, 2015)
The Driftless Dark Skies Initiative is training and supporting a cohort of a dozen astronomy educators who make use of the unique resources of the Kickapoo Valley Reserve to inspire and inform school groups and the public about the night sky and space exploration by offering nature programs and public star parties.